Sentiment analysis of China’s “one-belt one-road” initiative and its effects on China’s soft power - Choong, Heng Hui; Abdullah, Salwani; Goh, Hong Lip; Lee, Pei May (2022)
This paper is a multidisciplinary study that incorporates the methods and concepts of computer science and political science in gauging the Malaysian public’s opinions of the One Belt One Road (OBOR) initiative—later rebranded as the Belt Road Initiative [BRI])—and assessing the relations between the BRI and China's soft power. The objective of this study is to develop an algorithm to conduct sentiment analysis on Twitter posts from 2019. This lexicon-based analysis process consists of five main steps: data collection, pre-processing, lexicon analysis, statistical analysis and presenting the analysis results. The study collected 1, 860 tweets related to the OBOR/BRI, of which, after data cleaning was conducted, 874 tweets remained. The sentiment analysis results show that the sentiment regarding the OBOR/BRI was generally positive (49.89%), and neutral sentiments and negatives sentiment were at 36.96% and 13.18%, respectively. The concept of using soft power to evaluate the results of sentiment analysis was incorporated into the study. Such an approach can broaden the scope of research to include discussions on the extent to which the BRI has helped China project its soft power, and how it could potentially be mobilised to enhance its soft power even further. This paper argues that, though the Malaysian public felt generally optimistic about the BRI, more can be done to increase the initiative’s positive image, thus China's soft power, through cultural interaction and exchange.